2019
DOI: 10.1590/0100-6991e-20192256
|View full text |Cite
|
Sign up to set email alerts
|

Câncer gástrico em adultos jovens: um grupo de pior prognóstico?

Abstract: RESUMO Objetivo: avaliar as características clínico-patológicas e sobrevivência de pacientes jovens, portadores de câncer gástrico, independentemente da intenção de tratamento. Métodos: análise retrospectiva de todos os pacientes com câncer gástrico submetidos a qualquer tratamento cirúrgico entre 2008 e 2017. Pacientes com idade inferior a 45 anos foram considerados adultos jovens, e aqueles com mais de 45 anos foram definidos como grupo com idade avançada. Resultados: dos 875 pacientes avaliados, 84 (9,6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
3
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
2
6
3
10
Order By: Relevance
“…The Lauren classification demonstrates numerous differences in etiology, epidemiology and pathology of gastric cancer and diffuse type gastric carcinomas often show a poor prognosis. [24][25][26][27] We observed that diffuse type gastric cancers have a poorer prognosis with shorter overall survival compared to intestinal type gastric cancer, consistent with the literature. Regarding tumor grade, we had conflicting results as we found a significant association between tumor grade and prognosis in Kaplan-Meier analysis and no significant association between tumor grade and survival in univariate and multivariate analyses.…”
Section: Discussionsupporting
confidence: 91%
“…The Lauren classification demonstrates numerous differences in etiology, epidemiology and pathology of gastric cancer and diffuse type gastric carcinomas often show a poor prognosis. [24][25][26][27] We observed that diffuse type gastric cancers have a poorer prognosis with shorter overall survival compared to intestinal type gastric cancer, consistent with the literature. Regarding tumor grade, we had conflicting results as we found a significant association between tumor grade and prognosis in Kaplan-Meier analysis and no significant association between tumor grade and survival in univariate and multivariate analyses.…”
Section: Discussionsupporting
confidence: 91%
“…GC patients were commonly classified into a young group and an old group; however, the cutoff value of age was different [8,9]. In this study, we chose 45 years of age as the cutoff age for analysis, which was consistent with the majority of previous studies [18][19][20].…”
Section: Discussionmentioning
confidence: 78%
“…Younger patients have fewer comorbidities and a higher tolerance for surgery and adjuvant chemotherapy than older patients [11,12]. Additionally, they can undergo intensive chemotherapy followed by gastrectomy with adequate lymph node dissection, which improves long-term prognosis [13,14]. However, some young patients present with rapidly progressive disease and distant metastasis.…”
Section: Introductionmentioning
confidence: 99%